"TECHNOLOGIES FOR DEVELOPING CADETS' PROFESSIONAL AND PERSONAL TRAINING THROUGH MEDIA-DIDACTIC TOOLS" - D. T. Pulatov (Modern American Journals, 2025)
This article analyzes the technologies for developing cadets' professional and personal training using media-didactic tools. With the rapid advancement of modern information and communication technologies, multimedia capabilities are being widely integrated into the educational process. The article discusses how these tools enhance theoretical knowledge, practical skills, and personal growth. The integration of media-didactic tools into the teaching process plays a critical role in improving cadets' decision-making, stress resistance, and teamwork abilities.
Keywords: Media-didactic tools, cadets, professional training, personal development, educational technologies.